Screw cleaning material additive, preparation method thereof and screw cleaning material

By using anionic surfactant, anti-redeposition agent and specific inorganic salts in the screw cleaning material additive, efficient cleaning of the injection molding machine screw is achieved, solving the problems of high material consumption and low cleaning efficiency in the prior art, reducing costs and improving cleaning effect.

CN119875206APending Publication Date: 2025-04-25ZHUHAI GREE NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510015329.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art consumes a lot of materials when cleaning the screw of the injection molding machine, which consumes a lot of time, is low in efficiency and is cost-effective. Commonly used cleaning materials such as PP and LDPE are difficult to effectively clean up sediments during the cleaning process, resulting in less obvious cleaning effect.

Method used

A screw cleaning material additive is used, which contains anionic surfactant, anti-redeposition agent and specific inorganic salts, such as calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate, and the cleaning effect is improved through physical cleaning and chemical reaction.

Benefits of technology

The screw cleaning material additive achieves a more efficient cleaning effect through the combination of inorganic salts and the effect of anionic surfactant, avoids damage to machine parts by glass fiber and other materials, reduces production costs, and improves the comprehensive performance of cleaning material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875206A_ABST
    Figure CN119875206A_ABST
Patent Text Reader

Abstract

The invention specifically discloses a screw cleaning material auxiliary agent, a preparation method and a screw cleaning material, the screw cleaning material auxiliary agent comprises an anionic surfactant, an anti-redeposition agent and inorganic salt, and the inorganic salt is two or more of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate. Specific inorganic salts are adopted, mutual adsorption and lubrication among all the components are achieved through cooperation of different inorganic salts, and the cleaning effect of the screw cleaning material auxiliary on a screw is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a screw cleaning material additive and a preparation method thereof, and a screw cleaning material. Background Art

[0002] Injection molding machine is a commonly used plastic processing equipment. Its screw is one of the important parts in the injection molding machine, which is used to melt, mix and extrude plastic materials. When the machine is changing molds to change products or changing colors, and the product has mixed colors and black spots, it is necessary to clean the screw, material pipe and hot runner. The method adopted by most injection molding factories now is: using a large amount of raw material resin to repeatedly eject the material in the screw until the screw, material pipe and hot runner are clean. This cleaning method consumes a lot of materials, takes a long time, is inefficient, and has high costs, which has seriously affected production efficiency. In addition, plastics with excellent thermal stability, good fluidity and good adhesion to other resin materials are often used in the prior art to replace a large amount of raw material resin. For example, PP and LDPE are commonly used as alternative materials for cleaning materials of injection molding machine screws. However, in the case of material degradation and carbonization, it is difficult to clean the decomposed carbon deposited in the screw groove using PP or LDPE, and PP and LDPE themselves will also be retained in the screw groove, resulting in a large amount of PP and LDPE but the cleaning effect is not obvious. At present, the prices of screw cleaning materials sold on the market are generally high, often several times the prices of PP and LDPE. This is also the reason why there is a great demand for screw cleaning materials but the market sales volume is not large.

[0003] The patent application publication number CN 105924931A discloses a method for preparing an efficient plastic screw cleaning agent. However, a large amount of glass fiber is added therein, and the mechanical friction between the filler and the screw during use will accelerate the damage to the screw. In addition, these fillers have poor fluidity and poor compatibility with the resin, and serious self-residue will occur without the effect of shear force at the die head.

[0004] The patent application publication number CN107698865A discloses a method for preparing a screw cleaning material for an injection molding machine. The screw cleaning material is obtained by melt blending and extrusion granulation of a microcapsule auxiliary agent and a PP matrix resin in a certain ratio. However, the key component of the screw cleaning material prepared in the patent, the microcapsule auxiliary agent, is a core material emulsion made of urea-formaldehyde resin as the wall material and a mixture of butylene phthalate, ethylene glycol monophenyl ether and n-octanol as the core material. The microcapsules are finally prepared under a series of conditions, resulting in a complex process and high cost. The patent application publication number CN 114479250 A discloses a polyethylene screw cleaning agent and a preparation method thereof. However, when using, A is added first, and then composition B is added 5-15 minutes later depending on the carbon deposits on the screw or the attachment of colorants. Compared with adding the cleaning material all at once, the operation steps of this invention are cumbersome and inconvenient for users to use.

[0005] Therefore, the prior art needs to be further developed and improved. Summary of the invention

[0006] In view of the various deficiencies of the prior art and in order to solve the above problems, a screw cleaning material additive and a preparation method and a screw cleaning material are proposed. The present invention provides the following technical solutions: A screw cleaning material auxiliary agent comprises: an anionic surfactant, an anti-redeposition agent and an inorganic salt, wherein the inorganic salt is two or more of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate.

[0007] Furthermore, the inorganic salt is calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate.

[0008] Furthermore, the mass ratio of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is (7-9): (5-7): (3-5): (1-3).

[0009] Furthermore, the mass ratio of the calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is 8:6:4:2.

[0010] Furthermore, the anionic surfactant is one or two of polyoxyethylene lauryl ether phosphate, alkyl phosphate, and nonylphenol polyoxyethylene ether, and the anti-redeposition agent is one or two of hydroxymethyl cellulose and polyvinyl pyrrolidone.

[0011] Furthermore, the anionic surfactant is polyoxyethylene lauryl ether phosphate, and the anti-redeposition agent is hydroxymethyl cellulose and polyvinyl pyrrolidone.

[0012] Furthermore, the mass ratio of the hydroxymethyl cellulose to polyvinyl pyrrolidone is (4-7): (3-6).

[0013] Furthermore, calculated by weight, the anionic surfactant is 1-5 parts, the anti-redeposition agent is 1-5 parts, and the inorganic salt is 15-25 parts.

[0014] Furthermore, the screw cleaning material additive also includes a corrosion inhibitor and a lubricant, wherein the corrosion inhibitor is 1-3 parts and the lubricant is 0.2-1 parts.

[0015] In addition, the present application also provides a method for preparing a screw cleaning material additive, which is characterized in that the preparation method is as follows: first put an anti-redeposition agent, an inorganic salt and an anionic surfactant accounting for 50% to 70% of the total mass of the anionic surfactant into a high-speed mixer, stir for 0.3h-0.6h at 55-65°C and 800 r / min-1000r / min, then add the remaining anionic surfactant, and stir for 15-30min at 25-35°C and 1200-1500 r / min to obtain the screw cleaning material additive.

[0016] Furthermore, the anti-redeposition agent, the inorganic salt and the anionic surfactant accounting for 60% of the total weight of the anionic surfactant are firstly put into the high-speed mixer.

[0017] Furthermore, the anti-redeposition agent, the inorganic salt and the anionic surfactant (50-70% by weight of the total weight of the anionic surfactant) were first placed in a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining anionic surfactant was added and stirred at 30°C and 1300 r / min for 15 min.

[0018] The present application also provides a screw cleaning material, comprising: polypropylene resin, polypropylene recycled material and the above-mentioned screw cleaning material additive.

[0019] Furthermore, calculated by weight, the polypropylene resin is 45-60 parts, the polypropylene recycled material is 10-20 parts, and the screw cleaning material additive is 18-33 parts.

[0020] Beneficial effects: 1. The screw cleaning material additive provided in this application improves the comprehensive performance of the screw cleaning material by virtue of the synergistic effect of its physical cleaning and chemical reaction, and does not contain raw materials such as glass fiber that may damage the machine parts to be cleaned.

[0021] 2. Specific inorganic salts are used in this application, and different inorganic salts are matched to achieve mutual adsorption and lubrication between the components, further improving the cleaning effect of the screw cleaning material additive on the screw.

[0022] 3. The preparation method of the screw cleaning material additive provided in the present application adopts the method of adding key raw materials step by step, adding the anionic surfactant twice, preliminarily mixing with other raw materials under specific conditions, and adding the second time at low temperature and high speed to complete the final reaction. This step-by-step addition method can effectively control the reaction process and product microstructure, avoid agglomeration or local overreaction that may be caused by one-time addition, greatly improve the uniformity and efficiency of the screw cleaning material additive, and is a unique innovation of the preparation process.

[0023] 4. The preparation method of the screw cleaning material additive provided in this application adopts staged temperature and speed control. High temperature and low speed initially activate the activity of the raw materials and initially mix them, and low temperature and high speed promote the deep fusion and dispersion of key raw materials. The precise temperature and speed switching overcomes the problems of uneven mixing and insufficient reaction caused by a single temperature and speed, thereby significantly improving product performance and stabilizing quality.

[0024] 5. The screw cleaning material provided in this application is obtained by mixing a screw cleaning material additive with polypropylene resin and polypropylene recycled material. The recycled material resin is used as one of the main materials of the screw cleaning material, which expands the application research of plastic recycled materials in the field of screw cleaning materials, reduces production costs, and achieves sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram of the screw cleaning material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments in this application, other similar embodiments obtained by ordinary technicians in this field without making creative work should all fall within the scope of protection of this application. In addition, the directional words mentioned in the following embodiments, such as "up", "down", "left", "right", etc., are only reference to the directions of the accompanying drawings. Therefore, the directional words used are used to illustrate rather than limit the invention.

[0027] A screw cleaning material auxiliary agent comprises: an anionic surfactant, an anti-redeposition agent and an inorganic salt, wherein the inorganic salt is two or more of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate. The invention selects specific inorganic salts, and realizes mutual adsorption and lubrication between the components by matching different inorganic salts, and makes the physical cleaning and chemical reaction of the screw cleaning material auxiliary agent cooperate, further improving the cleaning effect of the screw cleaning material auxiliary agent on the screw.

[0028] Sodium tripolyphosphate has good dispersibility and chelating ability. It enhances the stability and fluidity of the mixture by adsorption, lubrication, anti-agglomeration and moisture-proofing with calcium carbonate, magnesium carbonate and anhydrous sodium sulfate components. The adsorption mechanism includes physical adsorption and chemical adsorption. Among them, physical adsorption is: sodium tripolyphosphate has a large specific surface area and surface energy. There is a van der Waals force between the molecules on the surface of calcium carbonate and anhydrous sodium sulfate particles and the surface molecules of sodium tripolyphosphate, so that calcium carbonate and anhydrous sodium sulfate particles are adsorbed on the surface of sodium tripolyphosphate, thereby preventing the agglomeration of particles and improving the stability and fluidity of the mixture. Chemical adsorption is: the oxygen atoms in the sodium tripolyphosphate molecules have lone pairs of electrons, which can form coordination bonds with the metal ions in calcium carbonate and anhydrous sodium sulfate, thereby chemical adsorption occurs. This chemical adsorption makes the combination between them stronger, further enhances the stability of the mixture, and is also conducive to improving its fluidity.

[0029] Lubrication: Magnesium carbonate and anhydrous sodium sulfate can be adsorbed on the surface of other particles, acting like a lubricant. The crystal structure of magnesium carbonate enables it to form a "lubricating film" between particles, reducing the friction between particles and thus improving the fluidity of the mixture. Anhydrous sodium sulfate has a similar effect, which can make the surface of particles smoother and make the mixture flow more easily during processing (such as stirring, pouring, etc.).

[0030] Anti-agglomeration and moisture-proof effects: The presence of calcium carbonate and magnesium carbonate can increase the overall density and stability of the mixture and reduce agglomeration caused by external factors (such as vibration, temperature changes, etc.). The hygroscopicity of anhydrous sodium sulfate can prevent moisture from entering the system, avoiding agglomeration and stability degradation caused by the dissolution and crystallization of inorganic salts caused by moisture. Sodium tripolyphosphate can also prevent agglomeration to a certain extent through dispersion and chelation. They work together to enhance the stability and fluidity of the mixture.

[0031] Among them, anhydrous sodium sulfate has a large specific surface area and a strong polar functional group, which can effectively adsorb colored impurities on the surface of the screw during cleaning. At the same time, during the mixing process, it absorbs trace moisture in the mixture to prevent the components from agglomerating and maintain the free flow of the mixture.

[0032] Calcium carbonate has good filling and whitening effects, and it can also provide a certain hardness. During the mixing process, the calcium carbonate particles will rub and collide with each other, gradually achieving uniform dispersion.

[0033] Sodium tripolyphosphate is an inorganic salt with good dispersibility and chelating ability. It enhances the stability and fluidity of the mixture by adsorption, lubrication, anti-agglomeration and moisture-proofing with calcium carbonate, magnesium carbonate and anhydrous sodium sulfate.

[0034] When the inorganic salt is calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate, and their mass ratio is (7-9): (5-7): (3-5): (1-3), calcium carbonate plays a major role in stabilizing the structure of the mixture, providing a certain hardness and support for the cleaning material, and helping to scrape the residue on the screw. Within this ratio range, it can effectively play its role without affecting the role of other components due to excessive content. Magnesium carbonate can adjust the pH of the system, and its crystal structure helps to improve fluidity. An appropriate amount of magnesium carbonate can work synergistically with calcium carbonate to further stabilize the structure of the mixture and improve fluidity to a certain extent. The hygroscopicity of anhydrous sodium sulfate can prevent agglomeration caused by moisture and improve fluidity to a certain extent. This ratio can better play its moisture-proof and lubricating functions. Sodium tripolyphosphate is a key dispersing and chelating component, which enhances stability and fluidity through ion exchange and adsorption. Its ratio needs to be high enough to fully play its role, but too high may lead to increased costs and imbalances in other properties. More preferably, when the mass ratio of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is 8:6:4:2, they can better play their roles in dispersion, lubrication and moisture-proofing.

[0035] The anionic surfactant is one or two of polyoxyethylene lauryl ether phosphate, alkyl phosphate, and nonylphenol polyoxyethylene ether, and the anti-redeposition agent is one or two of hydroxymethyl cellulose and polyvinyl pyrrolidone. Polyoxyethylene lauryl ether phosphate, alkyl phosphate, is an anionic surfactant derived from a nonionic surfactant, with high viscosity and strong degreasing ability. Due to its high viscosity, it can stay on the surface for a long time, quickly penetrate and adhere to the residual carbon deposits or plastic surfaces, which is conducive to improving the cleaning effect. In addition, hydroxymethyl cellulose can effectively prevent the tiny particles and dirt generated by the friction and shearing of the inner wall of the screw and the barrel from being deposited on the screw and the barrel again during the cleaning process. Specifically, when polyoxyethylene lauryl ether phosphate and hydroxymethyl cellulose work together, the cleaning purpose is achieved through physical action and synergistic effect. Polyoxyethylene lauryl ether phosphate is responsible for cleaning and wetting, while hydroxymethyl cellulose forms a bridge between components through its long chain structure during the mixing process. The two interact with each other to enhance the cohesion and fluidity of the mixture, provide stability and adhesion, and can absorb and fix the loosened carbon deposits, residues and other dirt. This synergistic effect allows the cleaning material to form a uniform film on the surface of the screw, thereby better covering and penetrating the stains and residues on the surface of the screw, thereby enhancing the cleaning effect.

[0036] It is not only hydroxymethyl cellulose that has this bridging effect. For example, polyvinyl pyrrolidone can also have similar anti-redeposition and bridging functions. The bridging effect refers to the role of anti-redeposition agents (such as hydroxymethyl cellulose) in connecting different components in the cleaning material system. Just like a bridge, it connects the various parts to make the entire system more stable and effective.

[0037] The bridging mechanism using hydroxymethylcellulose as an example: Molecular structure basis: Hydroxymethyl cellulose is a high molecular compound with a long molecular chain and many hydroxyl groups (-OH) on the molecular chain. These hydroxyl groups are active sites that can interact with each other.

[0038] Connection with the cleaning component: In the solid screw cleaning material, polyoxyethylene lauryl ether phosphate is the main component of cleaning and wetting. The hydroxyl group of hydroxymethyl cellulose can form hydrogen bonds or van der Waals forces with some groups in the polyoxyethylene lauryl ether phosphate molecule (such as the oxygen atom in the ether bond or the phosphate part). In this way, the polyoxyethylene lauryl ether phosphate is "connected" to the molecular chain of hydroxymethyl cellulose, so that the cleaning component can be better dispersed in the system.

[0039] Connection with other solid particles: For dirt particles (such as carbon deposits, residues, etc.) generated during the cleaning process, the long chain of hydroxymethyl cellulose can be wrapped around these particles. This is because the flexibility of the molecular chain allows it to adapt to the shape of the dirt particles and adsorb the dirt particles to the molecular chain by physical adsorption. At the same time, because hydroxymethyl cellulose is connected to polyoxyethylene lauryl ether phosphate, the dirt particles are equivalent to being connected to the decontamination ingredients through the "bridge" of hydroxymethyl cellulose.

[0040] Forming a network structure to enhance stability: Numerous hydroxymethyl cellulose molecular chains are intertwined in the system, forming a complex network structure with polyoxyethylene lauryl ether phosphate salt and dirt particles. This network structure can enhance the cohesion of the cleaning material, so that the cleaning material forms a uniform film on the surface of the screw. For example, during the film formation process, the bridging effect of hydroxymethyl cellulose enables different components to be arranged in an orderly manner, avoiding the separation and precipitation of the components, thereby ensuring the uniformity and stability of the film, which is conducive to better covering and penetrating the stains on the surface of the screw.

[0041] The anti-redeposition agent can be a compound of hydroxymethyl cellulose and polyvinyl pyrrolidone: when used for screw cleaning, hydroxymethyl cellulose mainly absorbs dirt through its long chain structure to prevent its redeposition, while polyvinyl pyrrolidone can play an anti-redeposition role by forming a complex with dirt particles. The mass ratio of hydroxymethyl cellulose and polyvinyl pyrrolidone is (4-7): (3-6). For example, a combination of hydroxymethyl cellulose and polyvinyl pyrrolidone with a mass ratio of 6:4 can utilize the adsorption advantage of hydroxymethyl cellulose and the complexing ability of polyvinyl pyrrolidone to effectively prevent dirt from re-depositing on the screw surface.

[0042] Screw cleaning material additives also include corrosion inhibitors and lubricants.

[0043] Specifically, the corrosion inhibitor is selected from one or two of imidazoline oleate, polyaspartic acid, and sodium petroleum sulfonate. Compound of imidazoline oleate and polyaspartic acid: imidazoline oleate mainly prevents corrosion by forming a protective film on the surface of the screw, while polyaspartic acid inhibits corrosion by chelating metal ions. The mass fraction of imidazoline oleate can be 60% - 80%, and the mass fraction of polyaspartic acid can be 20% - 40%. For example, in the combination of 70% imidazoline oleate and 30% polyaspartic acid, imidazoline oleate forms a physical protective film, and polyaspartic acid chelates metal ions that may cause corrosion, and the synergistic corrosion inhibition effect is better.

[0044] Compounding of imidazoline oleate and sodium petroleum sulfonate: the mass fraction of imidazoline oleate can be 50% - 70%, and the mass fraction of sodium petroleum sulfonate can be 30% - 50%. For example, the combination of 60% imidazoline oleate and 40% sodium petroleum sulfonate, sodium petroleum sulfonate can assist imidazoline oleate in enhancing the protection of the screw surface, while improving the lubrication performance of the system and reducing the damage to the screw during the cleaning process.

[0045] Compounding of polyaspartic acid and sodium petroleum sulfonate: The mass fraction of polyaspartic acid can be 40% - 60%, and the mass fraction of sodium petroleum sulfonate can be 40% - 60%. For example, a combination of 50% each, the chelating effect of polyaspartic acid and the lubrication and protection of sodium petroleum sulfonate are combined to effectively prevent the screw from being corroded during the cleaning process.

[0046] The lubricant is a compound of one or both of vinyl bis stearamide and oleic acid amide. Vinyl bis stearamide molecules have polar amide groups. Therefore, vinyl bis stearamide is mainly used as a lubricating release agent in plastic processing to improve the quality of plastic products and the appearance of products. Secondly, it also plays the role of anti-sticking, anti-static, improving pigment dispersion and auxiliary stability.

[0047] In addition, the present application provides a method for preparing a screw cleaning material additive, and the preparation method is as follows: first put an anti-redeposition agent, an inorganic salt and an anionic surfactant accounting for 50% to 70% of the total mass of the anionic surfactant into a high-speed mixer, stir for 0.3h-0.6h at 55-65°C and 800 r / min-1000r / min, then add the remaining anionic surfactant, and stir for 15-30min at 25-35°C and 1200-1500 r / min to obtain the screw cleaning material additive.

[0048] First, the preparation method adopts a staged temperature and speed control method: a two-stage stirring mode of high temperature and low speed followed by low temperature and high speed is adopted. High temperature and low speed initially activate the activity of raw materials and initially mix them, while low temperature and high speed promote the deep fusion and dispersion of key raw materials. The precise temperature and speed switching overcomes the problems of uneven mixing and insufficient reaction caused by a single temperature and speed, which significantly improves product performance and stabilizes quality.

[0049] Secondly, the preparation method adopts the step-by-step addition of key raw materials: the anionic surfactant is added twice, initially mixed with other raw materials under specific conditions, and the second addition is done at low temperature and high speed to complete the final reaction. This step-by-step addition method can effectively control the reaction process and product microstructure, avoid agglomeration or local overreaction that may be caused by one-time addition, and greatly improve the uniformity and efficiency of the screw cleaning material additive.

[0050] More specifically, anti-redeposition agent, inorganic salt and anionic surfactant (50-70% of the total mass) are first placed in a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining anionic surfactant is added, and stirred at 30°C and 1300 r / min for 15 min to obtain a screw cleaning material additive. Calcium carbonate, sodium tripolyphosphate, imidazoline oleate, hydroxymethyl cellulose, polyvinyl pyrrolidone, vinyl bisstearamide, polyoxyethylene lauryl ether phosphate salt and anhydrous sodium sulfate and magnesium carbonate are creatively selected to construct a composite system. The raw materials interact with each other under a specific process to form a unique physical and chemical structure, giving the screw cleaning material additive excellent comprehensive properties such as decontamination, dispersion, and anti-deposition in cleaning applications, which is different from the traditional single or simple combination of raw materials, and opens up new ideas for the formulation of cleaning material additives.

[0051] 1. Impact on reaction process: Initial stage: In the first step of mixing, after the polyoxyethylene lauryl ether phosphate salt is partially added, it can undergo preliminary physical mixing and chemical interaction with other raw materials such as calcium carbonate and sodium tripolyphosphate under the conditions of 60°C and 800r / min. This temperature is conducive to activating the molecular movement between the raw materials, allowing them to contact each other and start some weak interaction reactions such as hydrogen bonds and ionic bonds. Later stage: When the polyoxyethylene lauryl ether phosphate salt is added for the second time, the system has undergone preliminary mixing under the conditions of 30°C temperature and 1300r / min speed. The ester salt added at this time can more accurately participate in the reaction that needs to be further improved. Low-temperature and high-speed stirring can make the newly added ester salt quickly disperse and combine with the previous reaction products to avoid overreaction or side reactions. This step-by-step addition method can control the rate of the reaction so that it can proceed at a suitable speed in both stages to ensure that the reaction is sufficient and orderly.

[0052] 2. Influence on product microstructure Preventing agglomeration: If all polyoxyethylene lauryl ether phosphate salts are added at once, agglomeration may occur in the early stage of the reaction due to excessive local concentration due to their high surface activity. Adding them twice can effectively avoid this situation. When added for the first time, the ester salts are initially dispersed surrounded by other raw materials, and their concentration is relatively low, so they can be evenly distributed in the system. When added for the second time, the system already has a certain structural foundation, which can better accommodate the newly added ester salts and make them evenly integrated into the microstructure.

[0053] Build a uniform microstructure: This step-by-step addition method helps to build a more ordered and uniform microstructure. After the first mixing, some primary aggregates and chemical bonds have been formed in the system. After the second addition of the ester salt, under low-temperature and high-speed stirring, it can interact better with these primary structures, fill in the gaps in the microstructure or reorganize with the existing chemical bonds, thereby forming a more compact and uniform microstructure. The ester salt can form a more stable cross-linked structure with hydroxymethyl cellulose, improve the stability and performance of the product, and make the final screw cleaning material additive present a uniform and free-flowing powder state.

[0054] The screw cleaning material additive is preliminarily mixed with the polypropylene resin and the polypropylene recycled material in a mixer according to a certain proportion, and then processed in a twin-screw extruder to obtain the screw cleaning material.

[0055] Example 1 According to the mass parts, 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 8 parts of calcium carbonate, 6 parts of sodium tripolyphosphate, 4 parts of anhydrous sodium sulfate, 2 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 50% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1200 r / min for 15 min to obtain a screw cleaning material additive.

[0056] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0057] Example 2 Calculated by mass, 2.7 parts of hydroxymethyl cellulose, 2.3 parts of polyvinyl pyrrolidone, 7 parts of calcium carbonate, 5 parts of sodium tripolyphosphate, 3 parts of anhydrous sodium sulfate, 1 part of magnesium carbonate, 1 part of imidazoline oleate, 0.2 parts of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1300 r / min for 15 min to obtain a screw cleaning material additive.

[0058] Then, according to the mass proportions, 27.2 parts of the prepared screw cleaning material additive, 45 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: 170°C in zone 1, 180°C in zone 2, 180°C in zone 3, 185°C in zone 4, 190°C in zone 5, 190°C in zone 6, 180°C in zone 7, 180°C in zone 8, 185°C in zone 9, 195°C in zone 10, die head 195°C, speed of 400 r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0059] Example 3 According to the mass proportions, 0.57 parts of hydroxymethyl cellulose, 0.43 parts of polyvinyl pyrrolidone, 9 parts of calcium carbonate, 7 parts of sodium tripolyphosphate, 5 parts of anhydrous sodium sulfate, 3 parts of magnesium carbonate, 2 parts of imidazoline oleate, 0.5 parts of vinyl bisstearamide and 70% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, and stirred at 55°C and 800 r / min for 0.3 h. Then, the remaining polyoxyethylene lauryl ether phosphate was added and stirred at 35°C and 1200 r / min for 15 min to obtain a screw cleaning material additive.

[0060] Then, according to the mass proportions, 28.5 parts of the prepared screw cleaning material additive, 55 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: 170°C in zone one, 180°C in zone two, 180°C in zone three, 185°C in zone four, 190°C in zone five, 190°C in zone six, 180°C in zone seven, 180°C in zone eight, 185°C in zone nine, 195°C in zone ten, die head 195°C, speed of 400 r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0061] Example 4 According to the mass parts, 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 8 parts of calcium carbonate, 6 parts of sodium tripolyphosphate, 4 parts of anhydrous sodium sulfate, 2 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 65°C and 1000 r / min for 0.6 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 25°C and 1500 r / min for 30 min to obtain a screw cleaning material additive.

[0062] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 60 parts of polypropylene resin and 10 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0063] Example 5 Calculated by mass, 3 parts of hydroxymethyl cellulose, 7 parts of calcium carbonate, 5 parts of sodium tripolyphosphate, 3 parts of anhydrous sodium sulfate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 70% of the total mass of alkyl phosphate were first put into a high-speed mixer, stirred at 55°C and 800 r / min for 0.3 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 35°C and 1200 r / min for 15 min to obtain a screw cleaning material additive.

[0064] Then, according to the mass proportions, 25 parts of the prepared screw cleaning material additive, 55 parts of polypropylene resin and 15 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0065] Example 6 Calculated by mass, 3 parts of polyvinyl pyrrolidone, 15 parts of calcium carbonate, 10 parts of sodium tripolyphosphate, 2 parts of imidazoline oleate, 0.5 parts of vinyl bisstearamide and 60% of the total mass of nonylphenol polyoxyethylene ether were put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene dodecyl ether phosphate was added, and stirred at 35°C and 1500 r / min for 15 min to obtain a screw cleaning material additive.

[0066] Then, according to the mass proportions, 32.5 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: 170°C in zone one, 180°C in zone two, 180°C in zone three, 185°C in zone four, 190°C in zone five, 190°C in zone six, 180°C in zone seven, 180°C in zone eight, 185°C in zone nine, 195°C in zone ten, die head 195°C, speed of 400 r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0067] Comparative Example 1 Calculated by mass, 3 parts of hydroxymethyl cellulose, 20 parts of calcium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 3 parts of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then stirred at 30°C and 1200 r / min for 15 min to obtain a screw cleaning material additive.

[0068] Then, according to the mass fraction, 30 parts of the prepared screw cleaning material additive and 70 parts of polypropylene resin are mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix is ​​processed in a twin-screw extruder. The parameters of the screw extruder are: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400 r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0069] Comparative Example 2 According to the mass proportions, 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 3 parts of calcium carbonate, 3 parts of sodium tripolyphosphate, 3 parts of anhydrous sodium sulfate, 3 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, and stirred at 60°C and 800 r / min for 0.5 h. Then, the remaining polyoxyethylene lauryl ether phosphate was added and stirred at 30°C and 1200 r / min for 15 min to obtain a screw cleaning material additive.

[0070] Then, according to the mass proportions, 22 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0071] Comparative Example 3 According to the mass parts, 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 12 parts of calcium carbonate, 4 parts of sodium tripolyphosphate, 6 parts of anhydrous sodium sulfate, 1 part of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1000 r / min for 15 min to obtain a screw cleaning material additive.

[0072] Then, according to the mass proportions, 33 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0073] Comparative Example 4 Calculated by mass, 7 parts of hydroxymethyl cellulose, 10 parts of calcium carbonate, 10 parts of sodium tripolyphosphate, 10 parts of anhydrous sodium sulfate, 1 part of vinyl bisstearamide and 50% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1000 r / min for 15 min to obtain a screw cleaning material additive.

[0074] Then, according to the mass proportions, 45 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0075] Comparative Example 5 According to the mass proportions, 3 parts of hydroxymethyl cellulose, 20 parts of sodium tripolyphosphate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 80°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 50°C and 1000 r / min for 15 min to obtain a screw cleaning material additive.

[0076] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0077] Comparative Example 6 According to the mass proportions, 3 parts of hydroxymethyl cellulose, 20 parts of anhydrous sodium sulfate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 50°C and 700 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 45°C and 1000 r / min for 15 min to obtain a screw cleaning material additive.

[0078] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0079] Comparative Example 7 According to the mass proportions, 3 parts of hydroxymethyl cellulose, 20 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1000 r / min for 15 min to obtain a screw cleaning material additive.

[0080] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0081] Comparative Example 8 According to the mass proportions, 3 parts of hydroxymethyl cellulose, 25 parts of calcium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 40% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1300 r / min for 15 min to obtain a screw cleaning material additive.

[0082] Then, according to the mass proportions, 35 parts of the prepared screw cleaning material additive, 45 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0083] Comparative Example 9 According to the mass proportions, 3 parts of hydroxymethyl cellulose, 15 parts of calcium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 75% of the total mass of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate was added, and stirred at 30°C and 1300 r / min for 15 min to obtain a screw cleaning material additive.

[0084] Then, according to the mass proportions, 25 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0085] Comparative Example 10 Calculated by mass, 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 8 parts of calcium carbonate, 6 parts of sodium tripolyphosphate, 4 parts of anhydrous sodium sulfate, 2 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 3 parts of polyoxyethylene lauryl ether phosphate were first put into a high-speed mixer, and stirred at 60°C and 800 r / min for 45 minutes to obtain a screw cleaning material additive.

[0086] Then, according to the mass proportions, 30 parts of the prepared screw cleaning material additive, 50 parts of polypropylene resin and 20 parts of polypropylene recycled material were mixed in a mixer in proportion for 5 minutes to obtain a premix, and then the obtained premix was processed in a twin-screw extruder. The parameters of the screw extruder were: zone 170°C, zone 2 180°C, zone 3 180°C, zone 4 185°C, zone 5 190°C, zone 6 190°C, zone 7 180°C, zone 8 180°C, zone 9 185°C, zone 10 195°C, die head 195°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.

[0087] The screw cleaning material prepared in the above embodiments and comparative examples is used to clean the injection molding machine: the extruder performs normal switching (normal switching includes dark color to dark color, light color (or original color) to light color (or original color), light color (or original color) to dark color, etc.), and after the production is completed, the screw cleaning material is added to the extruder, and the cleaning is continued until the extrudate meets the color of the extruded rubber block and the raw material, and there are no color lines or black spots. At the same time, after proofing twenty mold parts, the appearance of the parts meets the process requirements, that is, the screw is cleaned, and finally the cleaning material usage and cleaning hours are recorded. The test results are shown in Table 1.

[0088] Table 1 Test results of the cleaning screws of the embodiments, comparative examples 2-10 and comparative example 1 (1) It can be seen from the results of the embodiments and comparative examples that 1.8 parts of hydroxymethyl cellulose, 1.2 parts of polyvinyl pyrrolidone, 8 parts of calcium carbonate, 6 parts of sodium tripolyphosphate, 4 parts of anhydrous sodium sulfate, 2 parts of magnesium carbonate, 3 parts of imidazoline oleate, 1 part of vinyl bisstearamide and 60% of the total weight of polyoxyethylene lauryl ether phosphate are stirred at 60°C and 800 r / min for 0.5 h, and then the remaining polyoxyethylene lauryl ether phosphate is added, and stirred at 30°C and 1300 r / min for 15 min to obtain a screw cleaning material additive, and then 30 parts of the prepared screw cleaning material additive is mixed with 60 parts of polypropylene resin and 10 parts of polypropylene recycled material according to the weight ratio to obtain the screw cleaning material with the best cleaning effect. That is, the mass ratio of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is (7-9):(5-7):(3-5):(1-3), and the mass ratio of hydroxymethyl cellulose and polyvinyl pyrrolidone is (4-7):(3-6).

[0089] (2) It can be seen from the results of Comparative Examples 2-3 and Comparative Examples 5-9 that when the ratio of inorganic salt exceeds the range covered by this application, the cleaning effect is greatly reduced.

[0090] (3) From the results of Comparative Example 4, it can be seen that when both hydroxymethyl cellulose and the surfactant are beyond the protection range, the cleaning effect is also reduced compared with the example.

[0091] (4) From the results of Comparative Example 10, it can be seen that when the inorganic salt is added separately and the temperature and speed are not controlled in stages, the cleaning effect is relatively lower than that of the embodiment.

[0092] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0093] The present invention has been described in detail above. The above description is only a preferred embodiment of the present invention and should not limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made within the scope of this application should still fall within the scope of the present invention.

Claims

1. A screw cleaning material additive, characterized in that: include: Anionic surfactant, anti-redeposition agent and inorganic salt, wherein the inorganic salt is two or more of calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate.

2. A screw cleaning material additive according to claim 1, characterized in that: The inorganic salts are calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate.

3. A screw cleaning material additive according to claim 2, characterized in that: The mass ratio of the calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is (7-9): (5-7): (3-5): (1-3).

4. A screw cleaning material additive according to claim 3, characterized in that: The mass ratio of the calcium carbonate, sodium tripolyphosphate, anhydrous sodium sulfate and magnesium carbonate is 8:6:4:

2.

5. The screw cleaning material additive according to claim 1, characterized in that: The anionic surfactant is one or two of polyoxyethylene lauryl ether phosphate, alkyl phosphate and nonylphenol polyoxyethylene ether; the anti-redeposition agent is one or two of hydroxymethyl cellulose and polyvinyl pyrrolidone.

6. A screw cleaning material additive according to claim 5, characterized in that: The anionic surfactant is polyoxyethylene lauryl ether phosphate, and the anti-redeposition agent is hydroxymethyl cellulose and polyvinyl pyrrolidone.

7. A screw cleaning material additive according to claim 6, characterized in that: The mass ratio of the hydroxymethyl cellulose to polyvinyl pyrrolidone is (4-7): (3-6).

8. The screw cleaning agent according to claim 1, characterized in that: Calculated by weight, the anionic surfactant is 1-5 parts, the anti-redeposition agent is 1-5 parts, and the inorganic salt is 15-25 parts.

9. A screw cleaning material additive according to claim 8, characterized in that: The screw cleaning material additive also includes a corrosion inhibitor and a lubricant, wherein the corrosion inhibitor is 1-3 parts and the lubricant is 0.2-1 parts.

10. A method for preparing the screw cleaning material additive according to any one of claims 1 to 9, characterized in that: The preparation method is as follows: first put an anti-redeposition agent, an inorganic salt and an anionic surfactant (50-70% of the total mass of the anionic surfactant) into a high-speed mixer, stir for 0.3-0.6h at 55-65°C and 800-1000r / min, then add the remaining anionic surfactant, stir for 15-30min at 25-35°C and 1200-1500r / min to obtain a screw cleaning material additive.

11. The method for preparing a screw cleaning material additive according to claim 10, characterized in that: First, put the anti-redeposition agent, inorganic salt and anionic surfactant accounting for 60% of the total weight of anionic surfactant into a high-speed mixer.

12. The method for preparing a screw cleaning material additive according to claim 10, characterized in that: First, put the anti-redeposition agent, inorganic salt and anionic surfactant (50-70% of the total mass of the anionic surfactant) into a high-speed mixer, stir at 60°C and 800 r / min for 0.5 h, then add the remaining anionic surfactant, and stir at 30°C and 1300 r / min for 15 min.

13. A screw cleaning material, characterized in that: include: Polypropylene resin, polypropylene recycled material and the screw cleaning material additive according to any one of claims 1 to 9.

14. A screw cleaning material according to claim 13, characterized in that: Calculated by weight, the polypropylene resin is 45-60 parts, the polypropylene recycled material is 10-20 parts, and the screw cleaning material additive is 18-33 parts.

Citation Information

Patent Citations

  • Efficient plastic screw cleaning agent, production method and use method

    CN105924931A

  • Preparation method of injection molding machine screw cleaning material

    CN107698865A

  • Polyethylene screw cleaning agent and preparation method thereof

    CN114479250A